REMITTING BEHAVIOUR OF ALBANIAN MIGRANTS: EVIDENCE FROM THESSALONIKI - Tavanxhiu, Manjola; Mancellari, Ahmet (European Scientific Journal, ESJ, 2015)
The aim of this research is to present a clear outline on the remitting behavior of Albanian migrants in the city of Thessaloniki. Since 1990, when the fall of communism created a big wave of emigration, remittances to Albania have been a vital source for this country but after 2008 financial crisis things have changed. The main topics of this paper is the exploration of the impact of the 2008 crisis in the level of remittances sanded toward Albania, as well as some evidence of the reason, methods of sending and purpose of their use. The empirical base of this research is a set of 200 indepth interviews with Albanian emigrants living in Thessaloniki. Material derives from an extensive period of fieldwork research conducted in Thessaloniki between May-June 2012.